Low-level laser therapy for the prevention of low salivary flow rate after radiotherapy and chemotherapy in patients with head and neck cancer - Gonnelli, Fernanda Aurora Stabile (Radiol Bras, 2016)
OBJECTIVE: To determine whether low-level laser therapy can prevent salivary hypofunction after radiotherapy and chemotherapy in head and neck cancer patients. MATERIALS AND METHODS: We evaluated 23 head and neck cancer patients, of whom 13 received laser therapy and 10 received clinical care only. An InGaAlP laser was used intra-orally (at 660 nm and 40 mW) at a mean dose of 10.0 J/cm(2) and extra-orally (at 780 nm and 15 mW) at a mean dose of 3.7 J/cm(2), three times per week, on alternate days. Stimulated and unstimulated sialometry tests were performed before the first radiotherapy and chemotherapy sessions (N0) and at 30 days after the end of treatment (N30). RESULTS: At N30, the mean salivary flow rates were significantly higher among the laser therapy patients than among the patients who received clinical care only, in the stimulated and unstimulated sialometry tests (p = 0.0131 and p = 0.0143, respectively). CONCLUSION: Low-level laser therapy, administered concomitantly with radiotherapy and chemotherapy, appears to mitigate treatment-induced salivary hypofunction in patients with head and neck cancer.